2018
DOI: 10.1186/s12938-018-0512-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of synthetic aperture architectures for miniaturised ultrasound imaging front-ends

Abstract: BackgroundPoint of care ultrasonography has been the focus of extensive research over the past few decades. Miniaturised, wireless systems have been envisaged for new application areas, such as capsule endoscopy, implantable ultrasound and wearable ultrasound. The hardware constraints of such small-scale systems are severe, and tradeoffs between power consumption, size, data bandwidth and cost must be carefully balanced.MethodsIn this work, two receiver architectures are proposed and compared to address these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Recent advances in medical imaging research have shown machine learning and artificial intelligence being used for image reconstruction. One such method is using a deep learning algorithm as a reconstruction method, as proposed by Kim et al (2020) and Peyton et al (2018). Kim et al (2020) worked on deep convolutional neural networks to overcome the issue of limited bandwidth and detection views, leading to severe structural loos and low image contrast.…”
Section: Signal Processing and Reconstruction Methodsmentioning
confidence: 99%
“…Recent advances in medical imaging research have shown machine learning and artificial intelligence being used for image reconstruction. One such method is using a deep learning algorithm as a reconstruction method, as proposed by Kim et al (2020) and Peyton et al (2018). Kim et al (2020) worked on deep convolutional neural networks to overcome the issue of limited bandwidth and detection views, leading to severe structural loos and low image contrast.…”
Section: Signal Processing and Reconstruction Methodsmentioning
confidence: 99%